Amazing spider-man (2022), volume 6 ebook Dead language, part 2. - Wells, Zeb (Amazing Spider-Man (2022), 2024)
Collects Amazing Spider-Man (2022) #24-26, Amazing Spider-Man Annual (2023) #1, Fallen Friend (2023) #1 and material from Free Comic Book Day 2023: Spider-Man/Venom (2023) #1. The shocking story it's all been building to - and your heart is not ready! At last, witness exactly what brought Peter Parker together with his former arch-nemesis, Norman Osborn as past and present collide with the return of the Emissary - and his power is far beyond Spider-Man's abilities. Peter and his allies may figure out a way to win, but the cost of victory will be so immense that you just might hope they don't! Plus: Witness the full fury of Peter's new Spidey suit unleashed! Discover how this year's Hellfire Gala impacts Spider-Man! And welcome back Hallows' Eve as she makes a play to break Chasm out of jail!